2000
DOI: 10.1046/j.1365-2826.2000.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Selective Effects of Oestradiol and Progesterone on NMDA and AMPA Receptors in the Rat Brain

Abstract: We investigated the effect of 10 months ovariectomy and a correction therapy, 2 weeks before the rats were killed, of oestradiol, progesterone or their combination on NMDA and AMPA receptor binding in the hippocampus, dentate gyrus, striatum, nucleus accumbens and frontal cortex of the rat brain as well as on amino acid levels in frontal cortex. NMDA and AMPA binding densities were assayed by autoradiography using, respectively, L-[3H]glutamate and [3H]AMPA; amino acid concentrations were measured by high perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 44 publications
4
66
2
Order By: Relevance
“…Our experiments showed that two weeks replacement therapy with estradiol decreased L-[ 3 H]glutamate specific binding in cingulate cortex, but not in the frontal or the parietal cortices. This confirms the regional specificity in the brain of estradiol on glutamate receptors that we previously reported (Cyr et al 2000a) and further refines the effect in the rostral cortex which is mostly in the cingulate cortex. NMDA receptors and L-[ 3 H]glutamate specific binding displayed a parallel pattern of changes after ovariectomy and estradiol treatment in the cingulate cortex, suggesting that the NMDA receptor is one of the glutamate receptor subtypes implicated in the hormonal modulation of L-[ 3 H]glutamate specific binding.…”
Section: Nmda Receptors Mrna Levelssupporting
confidence: 90%
See 4 more Smart Citations
“…Our experiments showed that two weeks replacement therapy with estradiol decreased L-[ 3 H]glutamate specific binding in cingulate cortex, but not in the frontal or the parietal cortices. This confirms the regional specificity in the brain of estradiol on glutamate receptors that we previously reported (Cyr et al 2000a) and further refines the effect in the rostral cortex which is mostly in the cingulate cortex. NMDA receptors and L-[ 3 H]glutamate specific binding displayed a parallel pattern of changes after ovariectomy and estradiol treatment in the cingulate cortex, suggesting that the NMDA receptor is one of the glutamate receptor subtypes implicated in the hormonal modulation of L-[ 3 H]glutamate specific binding.…”
Section: Nmda Receptors Mrna Levelssupporting
confidence: 90%
“…NMDA receptors and L-[ 3 H]glutamate specific binding displayed a parallel pattern of changes after ovariectomy and estradiol treatment in the cingulate cortex, suggesting that the NMDA receptor is one of the glutamate receptor subtypes implicated in the hormonal modulation of L-[ 3 H]glutamate specific binding. We have previously found a parallel pattern of changes in NMDA receptors and L-[ 3 H]glutamate specific binding in the cortical regions after ovariectomy and estradiol treatment (Cyr et al 2000a).…”
Section: Nmda Receptors Mrna Levelsmentioning
confidence: 85%
See 3 more Smart Citations